Siekierka typu Tautušiai z Bagienic Małych, pow. mrągowski, jako przykład złożoności i znaczenia przypadkowych znalezisk akwatycznych. - Joanna Urban (Przegląd Archeologiczny)
In this article, a single find of an axe of Tautušiai type from Bagienice Małe, Mrągowo district, is presented in a broad comparative background. The results of the stylistic-chronological analysis, attempts to objectify it, and the results of chemical studies of the alloy are presented. Consideration is also given to the function of this object both in the context of use (a tool, a weapon or a symbol of prestige) and its role and significance as an aquatic deposit.